Pengaruh Indek Pembangunan Manusia Dan Tingkat Pengangguran Terbuka Terhadap Tingkat Kemiskinan Di Kota Kediri Tahun 2019 - 2023 - Ersha Lintang Arum; Budi Heryanto; Bothy Dewandaru (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
Poverty is one of the fundamental problems that is a major concern in Indonesia. Data in Kediri City shows that there is an increasing fluctuation in poverty rates. One of the important indicators that affects poverty rates in Kediri City is the Human Development Index (HDI). The increase in poverty rates also occurs due to a decrease in the income of people who are laid off, resulting in a lot of unemployment. This study uses a quantitative method with data taken from the Central Statistics Agency (BPS). The results of the study show that the human development index (HDI) has an effect on poverty. And unemployment also has an effect on poverty. If the HDI and unemployment are combined, the results also have an effect on poverty in Kediri City.